PROPOSED FLEXIBLE PACKAGING PRODUCTION PERFORMANCE OPTIMIZATION: A CASE STUDY IN PT XX - Dwi Kurniawan, Ikhyan
The flexible packaging industry grows year after year, especially for PT XX. PT XX is engaged in Flexible Packaging, especially Biaxially Oriented Film. The polymers that are currently used are OPP and PET Resin. Once stretched transversely, the Jumbo Roll film will roll. Jumbo roll can be slitted into the intermediate roll and finished good Roll. The intermediate roll will be slitted into FG using a smaller machine or so-called secondary slitter. In a Primary slitter, the cutting process can immediately become finished good according to the customer's order. PT XX plans to add a new jumbo production machine in three years. To prepare and consider the need for new jumbo production machines, an analysis of the optimization of existing machines and resources is needed. Optimization is carried out related to the layout of the machine and the number of operators operating the machine. The problem that occurs during the interview is that there is not enough space to be able to do FG AD packing activities so that productivity and safety are optimal. After receiving the data, the observation results were made into a model in Arena simulation software. Running Arena simulation can be easier to understand and more positive results with better certainty (Radulescu, Tociu, & Radulescu, 2020). The parameters measured in this model are output quantity, utilization, and queue number. The result of the best scenario is the utilization value decreased by 6.67%. Decreased queue time value by 31.29% from the queue time existing model value. There was a decrease in the number of operators by 30.30%. Potential cost savings obtained amounted to IDR 44,72 Million with output quantity not reduced. This value significantly helps the production process more optimally.